Capital Investment as Investing in Organizational Capabilities: An Empirically Grounded Process Model - Maritan, Catherine A. (Academy of Management Journal, 2001)
This article describes a field study in which insights from the resource-based view of the firm were combined with models of capital investment decision making to investigate the decision processes used to make capital investments in capabilities. The study shows that different decision processes are used to invest in existing and new capabilities and that current models in the literature need to be adapted to capture the differences, which relate primarily to information requirements and management roles. The results suggest adopting a contingency approach to managing capital investment in capabilities.